Morphological characterization of Anticarsia gemmatalis M nucleopolyhedrovirus infection in haemocytes from its natural larval host, the velvet bean caterpillar Anticarsia gemmatalis (Hübner) (Lepidoptera : Noctuidae) - Silveira, Eni Braga da (2004)
For a better understanding of virus×host interactions, transmission electron microscopy was used to characterize the intrahaemocoelic infection of Anticarsia gemmatalis larval haemocytes by A. gemmatalisM nucleopolyhedrovirus (AgMNPV). At 12 h post-infection (h p.i.), we observed nuclear hypertrophy, budded virus assembling, and protrusion towards the cytoplasm, virion envelopment, and accumulation of fibrillar aggregates in the cytoplasm. Around 24 h p.i., fibrillar aggregates also appeared inside nuclei of infected cells. By 48 h p.i., virogenic stroma and polyhedra were visualised in nuclei and at 72 h p.i., widespread infection in haemocytes was observed. Cell remnants and free polyhedra were phagocytosed by granular haemocyte 1 and plasmatocytes. Entire cells were phagocytosed only by plasmatocytes. Necrosis of infected cells was quite common, suggesting a putative cytotoxic response. Granular haemocyte 1 presented a more exuberant protrusion of budded viruses in comparison to other haemocytes. All types of haemocytes were shown to be infected, and the intense virus replication in some of these cells reveals the importance of haemolymph for AgMNPV spread in its natural host, a critical factor for permissiveness.